DETERMINAN PENGUNGKAPAN LAPORAN KEBERLANJUTAN - Ardisa Safira; Pancawati Hardiningsih (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to analyze the effect of institusional ownership and firm size on sustinability report disclosure, with profitability as a moderating variable. This research applies a quantative approach using secondary data from annual report and sustainability resport of industrial sector comapnies listed on the Indonesia Stock Exchange (IDX) for the 2022-2023 period. The sample was selected using purposive sampling and anlyzed with multiple linier reggresion and moderated regrresion analysis (MRA). Sustainability disclosure was measured using GRI 2021 Standars. The results indicate that institusional ownership and profitability have a significant negative effect on sustainability report disclosure, while firm size has no significant effects. Futhermore, profitability is proven to moderated the relationship between institusional ownwership and sustainability disclosure by strengthening the negative effects. These findings highlight that companies tend to prioritize financial performance over sustainability transparancy, emphasizing the need for alignment between financial orientation and social and environmental accountability reporting.